Iodine-containing disinfectants in preparation for caesarean section: impact on thyroid profile in cord blood. Issue 1082 (26th October 2015) - Nili, Firoozeh; Hantoushzadeh, Sedigheh; Alimohamadi, Afsaneh; Shariat, Mamak; Rezaeizadeh, Golnaz
ABSTRACT: Background: Iodine-containing disinfectants are widely used for skin preparation before caesarean section. Current evidence suggests that maternal exposure to these disinfectants results in thyroid dysfunction in the newborns, but its extent is not known. Objectives: The purpose of this study was to explain the quality of the effect of these disinfectants on the thyroid function of newborns. Methods: This cohort study was performed on all the healthy mothers with a term pregnancy who underwent caesarean section in the obstetrics emergency department of an educational hospital affiliated with Tehran University of Medical Sciences from December 2013 to December 2014. We divided this 12-month period into two consecutive 6 months. Povidone–iodine 10% (PVP-I) and chlorhexidine gluconate 4% (CHX) were used in the first and second 6 months, respectively, for skin preparation before caesarean section and also for umbilical cord disinfection. Cord blood thyroid stimulating hormone (TSH) and thyroxine (T4) were assayed by the ELISA method. Results: We included 326 cases in this study, 153 in the PVP-I group and 173 in the CHX group. The incidence of cord blood TSH ≥10 mIU/L and T4 ≤7.3 µg/dL was significantly higher in the PVP-I than the CHX group. Cord blood TSH concentration showed a significant positive correlation with cord blood T4 concentration in the CHX group. Through selection of cases with cord blood T4 <13 µg/dL, we found a negative correlation between cord blood TSH and T4 concentration in the PVP-I group. Conclusions: It seems that PVP-I has the potential to cause false-positive screening-test results and increase recall rates, which should be evaluated in further studies. Trial registration number: Iranian Registry of Clinical Trials (IRCT) number IRCT201204289568N1.